An imaging photoelectron-photoion coincidence investigation of homochiral 2R,3R-butanediol clusters - Daly, Steven; Powis, Ivan; Garcia, Gustavo A.; Tia, Maurice; Nahan, Laurent (American Institute of Physics, 2017)
We report an experimental investigation of homochiral cluster formation in seeded molecular beam expansions of (2R,3R)-butanediol. Synchrotron radiation VUV photoionization measurements have been performed using a double imaging electron-ion spectrometer in various configurations and modes of operation. These include measurements of the cluster ion mass spectra and wavelength scanned ion yields and threshold electron spectra. Protonated cluster ions ranging up to n=7 have been observed and size-selected photoelectron spectra and photoelectron circular dichroism (PECD) have been recorded by velocity map imaging at a number of fixed photon energies. Translation temperatures of the cluster ions have been further examined by ion imaging measurements. As well as the sequence of protonated clusters with integral numbers of butanediol monomer units, a second series with half-integral monomer masses is observed and deduced to result from a facile cleavage of a butanediol monomer moiety within the nascent cluster. This second sequence of half-integral masses displays quite distinct behaviours. PECD measurements are used to show that the half-integral mass clusters ions do not share a common parentage with whole integer masses. Using an analogy developed with simple theoretical calculations of butanediol dimer structures, it is inferred that the dissociative branching into integral and half-integral ion mass sequences is controlled by the presence of different butanediol monomer conformations within the hydrogen bonded clusters.